Bioavailability of Major Minerals from Commonly Used Ruminants Feeds Using Dialyzability Technique - Singh, Abhilasha; Mani, Veena; Shukla, Bhawana; Kujur, Anjila; Kapila, Suman (Indian Journal of Animal Nutrition, 2019)
An in vitro study was conducted to assess the bioaccessibility (as a measure of bioavailability of minerals without animal modal) of calcium, phosphorous, magnesium, sodium and potassium by dialyzability technique. Four feeds maize grain (Zia mays), deoiled rice bran (Oryza sativa), groundnut cake (Arachis hypogaea) and mustard cake (Brassica campestris) were included for this study. Each test feed was dried, ground and chemically analyzed for proximate principles (Crude protein, Ether extract, Total ash, Crude fibre), and fiber fractions (Neutral detergent fibre and, Acid detergent fibre). Major mineral content was analyzed in dry ground sample by atomic absorption spectrometer. Three Karan- Fries calves were used for collection of rumen liquor through stomach tube. In vitro dry matter digestibility (IVDMD) of different samples was estimated at three stages i.e. simulating ruminal, abomasal and intestinal conditions, followed by determination of bioaccessibility of major minerals in the soluble fraction of intestinal stage sample through a 12kD dialyzable membrane, simultaneously a mock sample of rumen liquor with buffer solution also run. Results revealed that maize grain had significantly (P<0.05) highest (69.91±1.11) IVDMD value followed by mustard cake (68.51±1.087), groundnut cake (63.59±2.07) and deoiled rice bran (51.22±1.05) at the intestinal stage of digestion. A dialysis system was designed to model bioaccessibility of minerals, revealing that bioaccessible calcium, phosphorous and magnesium in maize grain significantly higher (71.76±1.66, 87.57±0.37 and 85.05±0.12 respectively) than that of mustard cake, groundnut cake and deoiled rice bran. These findings imply that increased utilization of maize grain might increase bioaccessible minerals in animals in tropical and warm temperate regions. Thus, it can be inferred from that finding in vitro method can be used for prediction of bioaccessible minerals fraction from feeds; however, validation by actual feeding is required before accepting the bioavailability values while considering these for dietary requirements.